DAMPAK PARIWISATA HIU PAUS TERHADAP LINGKUNGAN DI TELUK SALEH: STUDI PUSTAKA TENTANG UPAYA MENUJU PARIWISATA BERKELANJUTAN - Arisandi, Bobi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
The whale shark tourism in Saleh Bay, Indonesia, has become a significant attraction for both domestic and international visitors, providing substantial economic benefits to the local community. However, this increase in tourism activity has raised concerns about its environmental impacts. This study conducts a comprehensive literature review to assess the environmental impacts of whale shark tourism in Saleh Bay and explores strategies for achieving sustainable tourism practices. Findings indicate that whale shark tourism has led to behavioral disturbances in whale sharks, including changes in feeding and migratory patterns, as well as increased stress levels. Additionally, tourism activities have contributed to coral reef degradation and increased marine pollution. The study identifies key measures for mitigating these impacts, including enhanced tourist education, stringent regulations, environmentally-friendly infrastructure development, and community involvement. The recommendations aim to balance the economic benefits of whale shark tourism with the need for effective environmental conservation. This review provides a foundation for further research and policy development to support sustainable tourism in Saleh Bay, ensuring the protection of marine ecosystems while promoting local socio-economic growth.